Implementation of Humanist Concept in Music Learning at Qaryah Thayyibah Learning Community Salatiga - Taqi, Ahmad Yazid; Utomo, Udi; Cahyono, Agus (Universitas Negeri Semarang, 2021)
Humanist education is related to Ki Hajar Dewantara who is referred to as the Father of education. It prioritizes the humanitarian aspect by maximizing the potential of individuals, it is free, open and unbound. Qaryah Thayyibah Learning Community (KBQT) is a learning community that uses the learning method of student freedom in determining interest.This study was conducted to analyze and describe the application of humanist education concepts to music learning in the Qoryah Thayyibah Learning Community.The method used was a qualitative analytical method. Data collection techniques were carried out by observation techniques, interviews and document studies. Data analysis techniques were carried out with learning theory and humanist educational concepts.The results of the research on the application of humanist education concepts in music education in KBQT were conducted in terms of students as curriculum makers, discussion model learning, Gelar Karya (GK), and Final Project.This research can expand the reader's perspective on the importance of the learning process in KBQT, as it teaches the compactness among students, students and mentors, and sense of responsibility of students to determine their plans, and to be worked on.